Java 2 JSP and servlets - Griffith, Arthur; Virtual Training Company ([Australia] : Virtual Training Company, 2008)
JavaServer Pages and Java Servelets are programs executed by Web server to produce Web pages which are sent to a client Web browser in response to a request from the browser. This course demonstrate how to write them and shows how to deploy them to a server and make them run in response to a request
Title from container
Training CD
Contains 74 movies with total time 6 hours
System requirements: Mac: System 9 or higher ; PC: Windows 98 or higher, 32MB System RAM, 6MB Video RAM, 16x CD-ROM ; QuickTime 6
Keywords: Java (Computer program language); Servlets